Video modeling intervention for home use to improve social skills in children with ASD - Stankova, Margarita; Mihova, Polina; Kamenski, Tsveta; Naydenov, Encho; Vasileva, Veneta (Frontiers in Computer Science, 2026)
IntroductionThe article presents the design and development of a computer-supported video-modeling intervention for home use that aims to improve social skills in children with autism spectrum disorder (ASD).MethodsThe intervention was developed in several stages: researching the social needs of children with ASD through a parent’s survey and a focus group with specialists; writing scenarios; producing and technically designing the video; and creating a tutorial for implementing the intervention. During the first stage, parents, to a greater extent than specialists, emphasized the need to include language understanding and the use of language as a communication tool in the presentation of social skills. This approach placed the focus of the scenarios on dialogues and the use of words and expressions specific to social situations and further emphasized social communication.ResultsThe intervention introduced a new explanatory interactive modeling of social behaviors and a “visual coach,” a soft-spoken adult, who explains the social situation and repeats the important words and expressions that were present in the video. Furthermore, the intervention implied parental involvement and the possibility of training at home. Explanatory modeling supports parents by focusing the child’s attention on the most important moments in each social situation and repeating them. In this way, parents can follow the model and continue to perform activities with their children in a similar way for other social situations. The scenarios included three modules: communication with peers, communication with adults, and communication with both peers and adults. In preparing the recordings and their technical design, emphasis was placed on authentic settings and sounds, as well as on making the videos easy for the parents to use at home.DiscussionAn interactive element was introduced through the preparation of a guide for parents, in which specific instructions for each video enabled them to interact with the child within the topic, extending the learning of new skills beyond said video, and improve their communication with the child. As a result of the intervention, we expect that children will acquire the skills necessary for functioning in the most common social situations, by gaining a better understanding through explanatory modeling of why and how people act and what words and expressions they use to communicate and exchange information. We expect that this knowledge will help reduce children’s anxiety in social situations and give them more independence and confidence.